Conditional Deletion of Pdcd1 Identifies the Cell-Intrinsic Action of PD-1 on Functional CD8 T Cell Subsets for Antitumor Efficacy - Raghavan, Sukanya; Tovbis-Shifrin, Nataliya; Kochel, Christina; Sawant, Anandi; Mello, Marielle; Sathe, Manjiri; Blumenschein, Wendy; Muise, Eric S.; Chackerian, Alissa; Pinheiro, Elaine M.; Rosahl, Thomas W.; Luche, Hervé; et al. (Frontiers in Immunology, 2021)
PPD-1 blockade has a profound effect on the ability of the immune system to eliminate tumors but many questions remain about the cell types involved and the underlying mechanisms of immune activation. To shed some light on this, the cellular and molecular events following inhibition of PD-1 signaling was investigated in the MC-38 colon carcinoma model using constitutive (PD-1 KO) and conditional (PD1cKO) mice as well as in wild type mice treated with PD-1 antibody. The impact on both tumor growth and the development of tumor immunity was assessed. In the PD-1cKO mice, a complete deletion of Pdcd1 in tumor infiltrating T cells (TILs) after tamoxifen treatment led to the inhibition of tumor growth of both small and large tumors. Extensive immune phenotypic analysis of the TILs by flow and mass cytometry identified 20-different T cell subsets of which specifically 5-CD8 positive ones expanded in all three models after PD-1 blockade. All 5 subsets expressed granzyme B and IFNgamma. Gene expression analysis of the tumor further supported the phenotypic analysis in both PD-1cKO and PD-1 Ab treated mice and showed an upregulation of pathways related to CD4 and CD8 T cell activation, enhanced signaling through co-stimulatory molecules and IFN as well as non-T cell processes. Altogether, using PD-1cKO mice we define the intrinsic nature of PD-1 suppression of CD8 T cell responses in tumor immunity.